Revisioning the Central Delaware Riverfront: the effects of regime change on waterfront planning in Philadelphia, PA - Sergeant, Kathryn Lynn (Kansas State University, 2010)
This report will examine the effect that shifting political ideologies have had on the redevelopment process for Penn’s Landing and how citizen activism influenced planning reform along the Central Delaware Riverfront. It addresses the historical development that lead to the demise of Philadelphia’s port industry and waterfront commerce. The study discusses the influences that mayoral administrations from the 1950s to present day have had on planning for Penn’s Landing. The report reviews the public forums held by Penn Praxis to change the course of planning from a top-down approach to a grassroots effort and evaluates the progress that has been made in the years following the forums. An analysis of the political ideologies of Philadelphia’s mayoral administrations is made to determine that the most effective approach to advancing waterfront redevelopment along the Central Delaware Riverfront involves discovering the right balance of private investment and public involvement.
Keywords: Waterfront redevelopment; Philadelphia; Delaware River; Political Ideologies; Administration changes; civic engagement; Political Science, Public Administration (0617); Urban and Regional Planning (0999)